1987
DOI: 10.2307/1130524
|View full text |Cite
|
Sign up to set email alerts
|

The Stability of Visual Habituation during the First Year of Life

Abstract: The short-term reliability and long-term stability of visual habituation and dishabituation in infancy were assessed in a sample of 186 infants from 4 age groups (3-, 4-, 7-, and 9-month-olds) seen for 2 within-age sessions and in a sample of 69 infants seen longitudinally at 3, 4, 7, and 9 months of age. Moderate week-to-week reliability (r's = .30-.50) was observed for duration-based and magnitude of habituation variables at all ages, although better reliability was evident at 4 and 9 months than at 3 and 7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
52
1
2

Year Published

1989
1989
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(59 citation statements)
references
References 22 publications
4
52
1
2
Order By: Relevance
“…Two presentations of the same woman's smiling face (novelty stimulus) and 2 final trials of the same woman's neutral face (rehabituation) were presented following habituation. Faces have been used successfully as stimuli in several studies during the I st year of life (Colombo et al, 1987;Fagan, 1974).…”
Section: Methodsmentioning
confidence: 99%
“…Two presentations of the same woman's smiling face (novelty stimulus) and 2 final trials of the same woman's neutral face (rehabituation) were presented following habituation. Faces have been used successfully as stimuli in several studies during the I st year of life (Colombo et al, 1987;Fagan, 1974).…”
Section: Methodsmentioning
confidence: 99%
“…Based on these demonstrations of moderate, and not always consistent, correlations between mea sures, it would appear that if visual attention assessments are to be used in studies of developmental prediction, multiple assess ments would be preferable. This opinion has been expressed by Colombo et al [ 1987] and here by Slater et al They point out that the low correlations reported from infancy to later childhood are probably due to the fact that the dependent measures used as predic tors were collected on one occasion only. As a final comment on reliability of measures, we cannot ignore the probable fact that many studies that do not show reliable corre lations between repeated measures do not get published [Lecuyer, this issue], and this may be the same for the studies on predic tion of later cognitive development from early assessment.…”
Section: Reliability Of Measuresmentioning
confidence: 78%
“…When correla tion are obtained, they are mostly of moder ate or low amplitude. As Colombo et al [1987] have concluded, 'findings of moder ate reliability suggest some internally consis tent process. However, the amount of vari ance accounted for by these estimates of reli ability never exceeded 28%.'…”
Section: Reliability Of Measuresmentioning
confidence: 92%
See 2 more Smart Citations